Neonatal Polycythemia in Children Welfare Teaching Hospital, Medical city complex, Baghdad - Hameed, Numan N.; Jalil, Ashraf I. (Journal of the Faculty of Medicine Baghdad, 2014)
Backgroun1d: Polycythemia is defined as a central Hematocrit of at least 65%. Its` incidence is increased in babies who have intrauterine growth restriction (IUGR), are small for gestational age (SGA), and are born post term.  Many infants with polycythemia are asymptomatic. However, it may be associated with feeding problems and lethargy.   Objectives: This work aimed to study the polycythemic neonates admitted to neonatal care unit in children welfare teaching hospital, medical city complex, Baghdad, including demographic features, risk factors, management and early outcome.Patients and Methods: A descriptive study was carried out over 8 months period from 10th of April to the 10th of December 2012, on 50 neonates with polycythemia. The information collected including; age, sex, gestational age, birth weight, risk factors, clinical presentations, management and early outcome. All collected information were taken from patient's medical records, mothers, relatives of patients& residents in the neonatal care unit.Results: Males were more affected than females with male: female ratio of 1.6:1, irritability was present in 11(22%), Tachypnea 21(42%), Respiratory distress 14(28), Cyanosis 11(22%), Feeding disturbance 28(56%), Jaundice 5(10%), Hypoglycemia 15(30%), and thrombocytopenia in 4(8%). the risk factors include Hypertensive mother in 7(14%), diabetic mother 12(24%), twin pregnancy 7(14%). The gestational age:  18(36%) were term, 8(16%) were preterm, 24(48%) were post term. Regarding birth weight 9(18%) were Appropriate for gestational age, 32(64%) were Small for gestational age, 9(18%) were large for gestational age. The complications include seizure 4(8%), necrotizing enterocolitis 3(6%), renal failure in 2(4%). Partial exchange transfusion (PET) was done to 10 (20%). The early outcome include 36(72%) were discharged well, 5(10%) were discharged on family responsibility, 4(8%) were referred to other hospital, 3(6%) died.Conclusions: There is a male predominance in neonatal polycythemia. The most common and significant clinical finding was feeding problem. The most significant laboratory finding was hypoglycemia. The most significant risk factors are small for gestational age and Post term neonates. The outcome is generally good.